Association between the mid-upper arm circumference (MUAC) and calf circumference (CC) screening indicators of sarcopenia with the risk of pneumonia in stable patients diagnosed with schizophrenia - Ren, Silan; Huang, Sha; Chen, Ming; Zhu, Tian; Li, Qiuxia; Chen, Xiaoyan (Frontiers in Psychiatry, 2022)
Aim: Here, we investigate the relationship between mid-upper arm circumference (MUAC) and calf circumference (CC) screening indicators of sarcopenia and the risk of pneumonia in stable patients diagnosed with schizophrenia. Method: The study is prospective and includes inpatients with schizophrenia from two mental health centers in Western China. The studied screening indicators MUAC and CC were assessed in standing patients. The relationship between MUAC and CC as sarcopenia screening indicators with the risk of pneumonia in patients with schizophrenia was analyzed by performing a statistical logistic regression analysis. Result: Three hundred and thirty-nine patients with schizophrenia, aged 50 and over, were recruited for the study. Four patients with pneumonia that occurred within one week of the relapse of schizophrenia were excluded. As a result, only 335 patients were included in the analysis. Pneumonia has been reported in 82 (24.5%) of all included schizophrenic patients. Our data analysis confirmed that in the male patients the higher CC was associated with a lower risk of pneumonia (CC: OR=0.751, 95% CI: 0.635-0.889). We have divided the males into two cohorts following the values of CC. Our analysis further showed that the patients with CC<34 cm, had a lower risk of pneumonia in males (OR=0.36, 95%CI: 0.163-0.795). Conclusion: We demonstrate that CC is associated with pneumonia risk in stable males with schizophrenia.